A TCF4-dependent gene regulatory network confers resistance to immunotherapy in melanoma - Joanna Poźniak; Dennis Pedri; Ewout Landeloos; Yannick Van Herck; Asier Antoranz; Lukas Vanwynsberghe; Ada Nowosad; Niccolò Roda; Samira Makhzami; Greet Bervoets; Lucas F. Maciel; Carlos Ariel Pulido-Vicuña; et al. (2024)
To better understand intrinsic resistance to immune checkpoint blockade (ICB), we established a comprehensive view of the cellular architecture of the treatment-naive melanoma ecosystem and studied its evolution under ICB. Using single-cell, spatial multi-omics, we showed that the tumor microenvironment promotes the emergence of a complex melanoma transcriptomic landscape. Melanoma cells harboring a mesenchymal-like (MES) state, a population known to confer resistance to targeted therapy, were significantly enriched in early on-treatment biopsies from non-responders to ICB. TCF4 serves as the hub of this landscape by being a master regulator of the MES signature and a suppressor of the melanocytic and antigen presentation transcriptional programs. Targeting TCF4 genetically or pharmacologically, using a bromodomain inhibitor, increased immunogenicity and sensitivity of MES cells to ICB and targeted therapy. We thereby uncovered a TCF4-dependent regulatory network that orchestrates multiple transcriptional programs and contributes to resistance to both targeted therapy and ICB in melanoma.